New records of Pimelodella laticeps Eigenmann, 1917 (Siluriformes, Heptapteridae) and range expansion of its western distribution towards the Central Andes of Argentina - Valenzuela Gomez, Agustina Daniela (2023)
The lack of detailed knowledge about the diversity, distribution and biology of the fish in the province, together with the permanent introduction of exotic species such as salmonids, added to the anthropic activity associated to wetlands, threaten the conservation of the fish species richness. To date, for San Juan there is only a single report of P. laticeps collected in the Zonda department in Presidente Sarmiento Protected Natural Area. Specimens of P. laticeps are reported for the departments of Jachal, Ullum, Rivadavia, Zonda and Calingasta, expanding its distribution to its westernmost extreme towards the central Andes of Argentina.